A review on L2 models of reading theories and reading teaching strategy - Nizam Ahsani; Ahmad Budairi (International Journal of Education and Learning, 2022)
L2 reading instruction has tended to focus on the explicit teaching of reading strategies on the grounds that a strong grasp of reading strategies would lead to better reading comprehension skills. We argue that such teaching practice is very much anchored in the cognitive-psychological based theory of reading that have characterized the field of SLA over the years. In light of this, we seek to present a summary of various theories, research findings and arguments around the nature of reading in SLA. The data were collected through electronic database such as Eric, Google Scholar, Proquest and Wiley Online Library. We discuss three major reading models: bottom-up, top-down, and interactive model, alongside metacogniton theory, extensive and intensive reading as well as reading assessment. We believe that a sound understanding of these cognitive based processes underlying reading activity could serve as the basis for improvement in reading instruction. However, there is an inherent need to consider sociocultural aspects of reading in order to help students sustain reading engagement over an extended period of time toward the formation of reading habit. We conclude the discussion by suggesting that as reading actvity becomes increasingly digitized, more qualitative research studies exploring student’s individual experience are highly recommended, in complimentary to the cognitive-psychological based theory of reading.